Diastereo‐ and Enantioselective 1, 4‐Difunctionalization of Borylenynes by Catalytic Conjunctive Cross‐Coupling. Issue 26 (15th April 2020) - Law, Chunyin; Kativhu, Elton; Wang, Johnny; Morken, James P.
Abstract: Enantioselective conjunctive cross‐coupling of enyne‐derived boronate complexes occurs with 1, 4 addition of the electrophile and migrating group across the π system. This reaction pathway furnishes α‐boryl allenes as the reaction product. In the presence of a chiral catalyst, both the central and axial chirality of the product can be controlled during product formation. Abstract : Chiral allenes : 1, 4‐Addition of the migrating group and electrophile across an enyne‐derived boronate complex occurs during the course of Pd‐catalyzed conjunctive cross‐coupling. This process generates chiral allenyl boronic esters with control of both axial and central chirality.